(untitled) (Al-Aasar, 2025)
The philosophy of Khudi, articulated by Allama Muhammad Iqbal, serves as a cornerstone of his intellectual and poetic legacy. Khudi, which translates to "self" or "ego," encapsulates the essence of individual identity and internal strength. Iqbal posits that the awakening of Khudi is paramount for personal development and self-realization. According to him, a conscious understanding of one’s Khudi enables individuals to harness their true potential and shape their destinies. This philosophy also emphasizes the significance of divine love Ishq-e-Elahi) as a transformative force that elevates the human spirit. Iqbal further connects individual Khudi with collective identity, asserting that a robust self-awareness among individuals contributes to the strength of the community. His ideas encourage a balance between spiritual enlightenment and material pursuits, advocating for a holistic approach to life. Through Khudi, Iqbal calls for liberation from societal constraints, urging individuals to reclaim their agency. The philosophy of Khudi remains relevant today, inspiring contemporary discussions on self-identity, empowerment, and spiritual awakening. Ultimately, Iqbal’s vision offers a roadmap for individuals seeking to discover their inner selves while fostering a sense of collective purpose and national identity.